LEFT VENTRICULAR SYSTOLIC DYSFUNCTION PREDICTED BY EARLY TROPONIN I RELEASE AFTER ANTHRACYCLINE BASED CHEMOTHERAPY IN BREAST CANCER PATIENTS - Shafi, Azhar; Siddiqui, Neelam; Imtiaz, Saba; Sajid, Mansoor Ud Din (Journal of Ayub Medical College Abbottabad, 2017)
Background: Anthracyclines are one of the most effective chemotherapeutic agents in management of Breast cancer, however Anthracycline induced cardiotoxicity remains a matter of special concern. Detection of early toxicity by use of biomarkers like Troponins has been the focus of interest in recent years. We measured Troponin I levels after chemotherapy with anthracyclines and correlated it with ECG, Echocardiography and clinical findings. Methods: Patients with early Breast cancer eligible for chemotherapy were included in the study. All patients underwent clinical evaluation, Left Ventricular Ejection Fraction (LVEF) measurement by echocardiography at baseline and every 03 monthly for first year. Serum samples for TNI were obtained immediately after chemotherapy and after 24 hrs. Results: A total of 82 patients (all females) were included in the study. Median age was 47 (range 30-64) years. Anthracycline mediated cardiotoxicity occurred in 6 patients (7%) and was more frequent in patients with TNI elevation (p<0.001). Five patients (83%) recovered from cardiotoxicity. At multivariate analysis, TNI elevation was the only independent predictor of cardiotoxicity (95% CI 0.0007879 to 0.2821) and of lack of LVEF recovery (95% CI 0.002484 to 1.680). Conclusion: Measurements of Trop I levels after Anthracyclines can be useful in detecting early cardiotoxicity and tailoring further therapy. Keywords: Anthracyclines; Cardiotoxicity; Breast cancer; Troponin I; Left ventricular dysfunction